Bone Lake [videorecording (DVD)] - Friedlander, Joshua; Hasson, Maddie, 1995-; Roe, Alex, 1990-; Pigossi, Marco; Nechita, Andra (Decal, Bleecker Street, 2025)
A couple's vacation at a lakeside estate is upended when they are forced to share the mansion with a mysterious couple. A dream getaway spirals into a nightmarish maze of sex, lies, and manipulation, bringing terrifying secrets to light.